Histochemical differences along the intestine of Corydoras paleatus (Siluriformes: Callichthyidae) - Plaul, Silvia E. (2016)
The Neotropical catfish Corydoras paleatus is a facultative air-breather and the caudal half of the intestine is involved in gas exchange. In South America, air-breathing fishes are found in tropical or sub-tropical freshwaters where the probability of hypoxia is high. The aim of this study was to characterize by traditional histochemical and lectinhistochemical methods the pattern of carbohydrate in the intestinal mucosa. Intestine samples were taken from 25 healthy adult specimens collected in Buenos Aires (Argentina). Samples were fixed by immersion in 10 % buffered formalin and routinely processed and embedded in paraffin wax. Subsequently, these sections were incubated in the biotinylated lectins battery. Labeled Streptavidin-Biotin (LSAB) system was used for detection, diaminobenzidine as chromogen and haematoxylin as a contrast. To locate and distinguish glycoconjugates (GCs) of the globet cells, we used the following histochemical methods: PAS; PAS*S; KOH/PA*S; PA/Bh/KOH/PAS; KOH/PA*/Bh/PAS; Alcian Blue and Toluidine Blue at different pHs. Microscopically, the general structure of vertebrate intestine was observed and showed all the cell types characteristic of the intestinal epithelium. The cranial sector of catfish intestine is a site of digestion and absorption and its structure is similar to other fish groups. In contrast, enterocytes of the caudal portion are low cuboidal cells; and between these, globet cells and capillaries are observed, these latter may reach the mucosal lumen. Underlying the epithelium, observed a well-developed lamina propria-submucosa made of connective tissue; this layer was highly vascularized and did not exhibit glands. According to histochemistry, the diverse GCs elaborated and secreted in the intestine are associated with specific functions in relation to their physiological significance, with special reference to their role in lubrication, buffering effect and prevention of proteolytic damage to the epithelium together with other biological processes, such as osmoregulation and ion exchange. The lectinhistochemical analysis of the intestinal mucosa reveals the presence of terminal residues of glucose, mannose and galactose. In conclusion, this study has shown that GCs synthesized in the intestine of C. paleatus exhibit a high level of histochemical complexity and that the lectin binding pattern of the intestinal mucosa is characteristic of each species and the variations are related with the multiple functions performed by the mucus in the digestive tract. The information generated here may be a relevant biological tool for comparing and analyzing the possible glycosidic changes in the intestinal mucus under different conditions, such as changes in diet or different pathological stages.